Fighter in Velvet Gloves : Study Guide - Boochever, Annie (Book collections on Project MUSE., 2021)
""No Natives Allowed!" blared the storefront sign at the young Tlingit Indian girl. The sting of those words would stay with Elizabeth Peratrovich all her life. They would also make her deter-mined to work for change. Years later, a seasoned fighter for equality, she would deliver her own eloquent message, one that helped change Alaska and the nation forever. Writ-ten in collaboration with Elizabeth's eldest son and only living child, Roy Peratrovich Jr., Fighter in Velvet Gloves tells the life story of this inspirational Alaskan and American hero, for readers 10 and up. This book is intended as a study guide for teachers and students to use with Fighter in Velvet Gloves"--